Mirʾāt-i wāridāt : Tārīkh-i suqūṭ-i Ṣafawiyān, payāmadhā-yi ān wa farmānrawāyi-yi Malik Maḥmūd-i Sīstānī - Sistānī, Malik Maḥmūd (Miras Maktoob, ISBN: 9789004365452., 2019)
The final years of the reign of the Safavids (1501-1722) have been described by many (near-) contemporary authors. A key-event in this period was the rebellion of Malik Maḥmūd Sistānī who, in 1722, in exchange for recognizing Maḥmūd the Afghan as the new shah of Persia rather than doing battle with him in a last-ditch effort to liberate Isfahan, was allowed to claim sovereignty in Mashhad in Khurāsān-an independence which lasted until his defeat in November of 1726. In the standard Persian sources covering this episode, Malik Maḥmūd is described in negative terms, as an adventurer who had to be dealt with. The present work, written by a first-generation Indian of Persian descent, gives a much more positive description of Malik Maḥmūd and his claims to power, often providing hitherto unknown details. Most likely based on oral testimonies by followers who had fled to India, this a is welcome addition to the standard account.